RELEVANSI WAYANG KULIT SEBAGAI MEDIA DAKWAH DI ERA MODERN: Studi Tentang Media Dakwah - Agus Fatuh Wardoyo (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
In modern life, wayang can have a dual function, namely as a medium to fulfill spiritual needs and at the same time as entertainment. This is because modern humans experience alienation, which is a feeling of loneliness in the crowd around them. This is what makes wayang kulit remain relevant in the modern world to become a medium of da'wah. The art of wayang culture is the original work of the Indonesian people, especially Java. The art of wayang kulit is currently the identity of the Indonesian nation. Wayang in its current form is a precious heritage for Muslims.